Planar Solid Oxide Fuel Cells Using PSZ, Processed by Sequential Aqueous Tape Casting and Constrained Sintering. Issue 10 (4th September 2013) - Aguilar‐Arias, Jaime; Hotza, Dachamir; Lenormand, Pascal; Ansart, Florence; Menon, M.
<x xml:space="preserve">Abstract</x> A process for obtaining planar anode‐supported solid oxide fuel cells was developed. Aqueous‐based slurries were prepared and sequentially deposited via tape casting to form half cell tapes consisting of the electrolyte, functional, and structural anode. Sintering of the three‐layered tapes was done in two stages: presintering circular samples of 25 mm diameter in free conditions first, and then sintering them using zirconium disks as light loads (90 Pa), to obtain half cells having 20 mm and 3.8 m−1 in diameter and curvature, respectively. Active materials for the electrolyte, anode, and cathode were partially stabilized zirconia (PSZ), Ni and LSM, respectively. Finally, thicknesses of complete cells were 400, 30, 30, and 80 μm for the structural anode, functional anode, electrolyte, and cathode, respectively. The cells were tested in a no‐chamber (direct‐flame) setup evaluating electrochemical performance and shock thermal resistance. Open circuit voltage was 830 mV at 560°C using methanol as fuel in a burner with porous media to modify the shape of the flame. Cells were also strong enough to resist the rapid temperature changes during several no‐chamber tests.